Navigating an Interdisciplinary Horizon: Shaping the Future of Social Sciences. - Derek Layder (Global Journal of Human-Social Science, 2024)
A long fascination and publication history with both social theory and research methods eventually allowed me to develop a novel and unique platform of theoretical influences entangled social domains theory along with adaptive theory -which together form an appropriate and integrated package of research methods This involves four principle social domains which allow social researchers to effectively and simultaneously embrace multiple analytic angles perspectives and vantage points drawn from all areas of social science -on the same empirical data This package or platform is most useful for generating novel theory from research data about a vast range of areas of social life -industrial and professional management the adoption of disabled children 2018 chapters 6 and 7 through to popular culture body image and the use of gyms 2013 serial murder 2023a the exploration of mental health issues such as depression and anxiety and even the study of the relevance of creativity in social research